FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGGUNAAN KB IMPLANT DI KELURAHAN SEI PUTIH BARAT MEDAN TAHUN 2020 - Primanopa Situmorang; Masryna Siagian; Santy Deasy Siregar (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2020)
In terms of quantity, the use of implanted family planning in the Kelurahan Sei Putih Barat is in the quite low category compared to non-implantable acceptors. The lack of implant family planning acceptors is due to the many complaints experienced by implant KB acceptors. Of the 11 respondents surveyed, 7 of them experienced health complaints, namely experiencing menstrual disorders and experiencing problems with increasing body weight. This study aims to determine the factors associated with the use of implant family planning in Sei Putih Barat Village. This type of research is an analytical survey with a cross sectional research plan. The population of this study were all fertile age couples (PUS) who were in the West Sei Putih village, as many as 3239 PUS. The sample in this study was 97 family planning acceptors in the West Sei Putih sub-district of Darusalam Public Health Center using simple random sampling technique. The research data analysis was performed using the chi-square test (X2) at the 95% confidence level (Î± = 0.05). The results showed that there was a relationship between parity (p = 0.000), knowledge (p = 0.002) with the use of family planning implants in the Sei Putih subdistrict, while occupation (p = 0.324) was not related to the use of the implant family planning in Kelurahan Sei Putih medan. The conclusion of this study is that there is a relationship between parity and knowledge with the use of family planning implants in the West Sei Putih subdistrict, Medan, while occupation is not related to the use of the implant family planning in the West Sei Putih subdistrict, Medan. This study suggests that health workers provide an understanding of implanted KB to prospective KB acceptors.